2014
DOI: 10.5812/jjm.10127
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus DNA level Among the Seropositive Afghan Immigrants, Southern Iran

Abstract: Background:Diagnosis and control programs for infectious diseases among immigrants are the most important aspects of epidemiological studies for both origin and destination countries. Data about hepatitis B virus (HBV) infection among the Afghan immigrants in Iran is limited.Objectives:To the best of HBV treatment and prevention in Afghan immigrants in Iran, the present study was conducted to determine the virus DNA level, and the frequency of respective hepatitis B risk factors among the respective seropositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Previous studies reported that the prevalence of hepatitis B infections was higher among Afghan immigrants and that the higher rate of hepatitis B infections in eastern Iran could be associated with the number of Afghan immigrants (27, 28). Another study suggested that all immigrants, regardless of the time since they had left their home countries, should undergo screening for major transmissible infections (29).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies reported that the prevalence of hepatitis B infections was higher among Afghan immigrants and that the higher rate of hepatitis B infections in eastern Iran could be associated with the number of Afghan immigrants (27, 28). Another study suggested that all immigrants, regardless of the time since they had left their home countries, should undergo screening for major transmissible infections (29).…”
Section: Discussionmentioning
confidence: 97%
“…Another study suggested that all immigrants, regardless of the time since they had left their home countries, should undergo screening for major transmissible infections (29). Moreover, Behzadi et al recommended that HBV screening of immigrants should be take place at entrances to country borders (27). The same study strongly recommended free vaccination and treatment programs and improving the level of HBV knowledge among Afghan immigrants in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…Viral DNA was extracted from HBs Ag and/or HBc Ab reactive samples and subsequently tested for HBV DNA by quantitative real-time PCR assay, as previously described [16]. Samples with HBV-DNAemia were subjected to HBV genotyping test as described previously [17].…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of hepatitis B virus infection among Afghan immigrants was significantly higher than that among Iranians ( p = 0.046). The prevalence of hepatitis B in Afghan immigrants in Iran may be high due in particular to the greater prevalence of injection drug use among Afghan immigrants [ 70 ]. This may be an important reservoir of hepatitis B in Iran.…”
Section: Discussionmentioning
confidence: 99%